Endothelial Dll4 overexpression reduces vascular response and inhibits tumor growth and metastasization in vivo - Trindade, A. (2017)
This work was supported by the Portuguese Foundation for Science and Technology (FCT; http://www.fct.pt/index.phtml.en), Project PTDC/CVT/115703/2009 to AD; PTDC/SAU-ONC/116164/2009 and PTDC/SAU-ONC/121742/2010 to AT. DD, JG and LM are PhD students supported by grants SFRH/BD/29447/2006, SFRH/BD/73264/2010 and SFRH/BD/74229/2010 from FCT. AT is a Postdoctoral Researcher supported by grants SFRH/BPD/47079/2008 and SFRH/BPD/110174/2015 from FCT. CIISA has provided support through Project UID/CVT/00276/2013, funded by FCT. The funders had no role in study design, data collection and analysis, decision to publish, or preparation of the manuscript. Editor